Analisis Pengaruh Motivasi, Disiplin Kerja Dan Komitmen Karyawan Terhadap Prestasi Kerja Karyawan (Study Kasus Rsud Karanganyar) - Rimbani, Sylvia Era; , Dra. Rina Trisnawati, M.Si., Ph.D; , Drs.Syamsudin, MM (2015)
is study aimed to analyze the influence of motivation, discipline and commitment on employee performance. This research is a quantitative research. The sample in this study was 150 employees of RSUD Karanganyar using purposive sampling technique. Data was collected by the questionairre method. Data analysis techniques using multiple linear regression analysis. These research results showed that 1) Motivation have a significant effect on employee performance of RSUD Karanganyar, with the value of tcount 4,355 > ttable (1,976). 2) Discipline have a significant effect on employee performance of RSUD Karanganyar, with the value of tcount 4,122> ttable (1,976). 3) Employee commitment have a significant effect on employee performance of RSUD Karanganyar, with the value of tcount 3,706> ttable (1,976). Based on the result can be concluded that motivation, discipline and commitment effecting on employee performance at RSUD Karanganyar. Keywords: Motivation, Work Discipline, Employee Commitment, Employee Performance